Affective Behavior in Parent Couples Undergoing Couple Therapy: Contrasting Case Studies - Liekmeier, Esther; Darwiche, Joëlle; Pinna, Lara; Repond, Anne-Sylvie; Antonietti, Jean-Philippe (Frontiers in Psychology, 2021)
Being in a romantic relationship is characterized by a high degree of intimacy and affective involvement. Affective behavior indicates the emotional content in couple interactions and therefore promotes an understanding of the evolution of romantic relationships. When couples are also parents, their affective behavior reflects their romantic and coparental bonds. In this paper, we present an observation of parent couples’ affective behavior to document whether and how much it improved during couple therapy. Two contrasting cases of affective behavior evolution are included. Observational coding of affective behavior within pre- and post-intervention coparenting conflict discussion tasks was carried out to compute slopes of affective behavior for each partner with linear regression in both cases. In addition, the partners’ coparental satisfaction was evaluated through validated self-report questionnaires in pre- and post-intervention assessments; this helped document whether the partners’ coparental satisfaction was dissimilar between the two cases. Finally, a clinical analysis of both cases was realized with the contribution of the therapists to investigate possible differences within therapy sessions. Linear regression revealed a negative evolution of affective behavior for couple A in the pre-intervention assessment and a positive evolution in the post-intervention assessment. Couple B experienced a negative evolution of affective behavior in the pre- and post-intervention assessments. Results concerning coparental satisfaction differed: Couple A’s coparental satisfaction slightly increased, whereas couple B’s coparental satisfaction remained stable between the pre- and post-intervention assessments. The clinical analysis revealed that the interactional quality of couple A slightly improved within therapy sessions and that both partners succeeded in working together as coparents, notwithstanding their romantic distress. Couple B conveyed coparental distress and exhibited poor interactional quality throughout therapy sessions (e.g., repeated criticism and contempt). This study contributes to enriching the more traditional empirical research methods in the field of couple psychotherapy, as it takes into account microlevel affective changes within parent couples’ interactions in addition to self-reported data. Furthermore, the analysis of therapy sessions highlights the importance of working with affective behavior in couple therapy.